Court decisions on forcing to sign an employment contract: problems and prospects - Nikanava, Nataliya N. (Journal of the Belarusian State University. Law, 2023)
In the Soviet period of the development of labour law the idea of the possibility of forcing an employer to conclude an employment contract on the basis of a court decision in the event of an unreasonable refusal to hire a candidate became widespread. Despite the fact that this method of protecting the rights of a person who wishes to be hired is not directly provided for by the Labour Code of the Republic of Belarus, an indication of it was enshrined in part 2, clause 4 of the provision of the Plenum of the Supreme Court of the Republic of Belarus of 29 March 2001 No. 2 «On some issues of application labour law by the courts». The issue of the acceptability of such a method of protecting the rights of an employee as forcing an employer to conclude an employment contract became topical because of changing approaches and trends in the field of labour law, the adoption of the Law of the Republic of Belarus of 24 October 2016 No. 439-З «On enforcement proceedings», planned changes to art. 415 of the Civil Code of the Republic of Belarus and estimated adoption of the Code of Civil Procedure of the Republic of Belarus. The author concludes that in case of an unreasonable refusal to hire the choice of a method of protection is the prerogative of the plaintiff, forcing the employer to conclude an employment contract cannot be considered as the only or main method of protection, the decision on employment contract coercion must contain the necessary terms of such a contract. It is proposed to legislate the possibility of collecting in favour of the employee an amount equal to three times the nominal accrued average salary of employees of the Republic of Belarus for the month preceding the date of the unjustified refusal to hire.